Extrinsic sources of cholinergic innervation of the striatal complex: a whole-brain mapping analysis - Daniel eDautan; Daniel eDautan; Husniye eHacioğlu Bay; Husniye eHacioğlu Bay; J. Paul Bolam; Todor V. Gerdjikov; Juan eMena-Segovia; Juan eMena-Segovia (Frontiers Media S.A., 2016)
Acetylcholine in the striatal complex plays an important role in normal behavior and is affected in a number of neurological disorders. Although early studies suggested that acetylcholine in the striatum is derived almost exclusively from cholinergic interneurons, recent axonal mapping studies using conditional anterograde tracing have revealed the existence of a prominent direct cholinergic pathway from the pedunculopontine and laterodorsal tegmental nuclei to the dorsal striatum and nucleus accumbens. The identification of the importance of this pathway is essential for creating a complete model of cholinergic modulation in the striatum, and it opens the question as to whether other populations of cholinergic neurons may also contribute to such modulation. Here, using novel viral tracing technologies based on phenotype-specific fluorescent reporter expression in combination with retrograde tracing, we aimed to define other sources of cholinergic innervation of the striatum. Systematic mapping of the projections of all cholinergic structures in the brain (Ch1 to Ch8) by means of conditional tracing of cholinergic axons, revealed that the only extrinsic source of cholinergic innervation arises in the brainstem pedunculopontine and laterodorsal tegmental nuclei. Our results thus place the pedunculopontine and laterodorsal nuclei in a key and exclusive position to provide extrinsic cholinergic modulation of the activity of the striatal systems.